KAJIAN KRITIS TENTANG PERANAN YURISPRUDENSI DI DALAM PEMBARUAN HUKUM KELUARGA ISLAM DI INDONESIA - Rasdiyanah, Rasdiyanah (Jurnal Ar-Risalah, 2022)
The research result shows that jurisprudence in Indonesia as source of law although judges were not bound with the present jurisprudence, it was because Indonesia take up the system of civil law. The position of jurisprudence becomes very crucial in a country which takes up civil law as source of law like in Indonesia, especially when regulation is not suitable with the real situation or does not adjust faced case. Role of jurisprudence in the renewal of Islamic family law in Indonesia is a fact. It can be seen in some decisions in Supreme Court who published new law regulation such as Decisions of Supreme Court No. 137 K/AG/2007 about giving money in iddah time to a wife who demanded for divorce, Decisions Number 266 K/AG/2010 about shared wealth, Decisions No. 86 K/AG/1994 about equality between son and daughter in hampering uncle to receive legacy,  Decisions Number 16 K/AG/2010 about giving wajibah legacy to non moeslem wife.. Besides, before Islamic Law Compilation was arranged, jurisprudence had showed the roles in creating law which consisted renewal of Islamic family law. Even jurisprudence is also source of reference in formulating articles of Islamic law Compilation as INPRES No. 1 in 1991.